The Role of Vocational Education in the Student Career Development Process - Muslim; M. Giatman; Nurhasan Syah; Nuzul Hidayat; Wagino (Indonesian Journal Of Educational Research and Review, 2023)
Many students feel anxious about career prospects, so they are afraid that career insights in the field will not be achieved. The purpose of this study is to analyze the role of vocational education in the career development process, especially for students who are still full of doubts about their careers. This type of research is descriptive qualitative in the form of a Systematic Literature Review (SLR) to collect evidence based on research topics and support the development of evidence-based research. The stages in the SLR method are planning, conducting, and reporting. The subject of this study is the literature related to vocational education in the career development process. The results of the study found 5 major themes out of 98 articles that had been selected related to the topic under study. The role of vocational education regarding job characteristics, career maturity development services, career opportunities, ability to make career decisions, and vocational career development in the student career development process. It is hoped that the findings in this study will become information for future researchers, teachers, the wider community, and policy-making institutions, especially in Indonesia.